Measurement of orthodontic bracket debonding force on different teeth using a prototype device equipped with force sensitive resistor: an in-vitro and in-vivo study - Ahmed, Tamzid (2018)
Orthodontic bonding studies should emphasize more on testing the effect of oral environment on the wide range of orthodontic bracket-adhesive systems that are evolving regularly. Therefore, the objective of this present study is to introduce a prototype device capable of debonding orthodontic brackets and measuring the peak debonding force clinically by a calibrated force sensor mechanism. Ninety-nine (99) maxillary premolar samples were prepared for the in-vitro studies. Standardized bonding protocol was maintained by a single clinician utilizing 0.022 metallic brackets (HKS 3, Ortho Classic, McMinnville, USA), Transbond XT adhesive with Transbond Plus self-etching primer (3M Unitek, Monrovia, California, USA) and LED light curing (model- DB686, COXO, Guangdong, China) for 20 seconds. Sixty (60) samples were divided equally into two (2) groups for the validation study. For intra and inter-examiner reliability, thirty-nine (39) samples were equally divided into three (3) groups. The brackets were debonded after twenty-four (24) hours of bonding. Clinically, orthodontic bracket debonding forces were measured on 260 different teeth in thirteen (13) patients after comprehensive fixed orthodontic treatment and divided equally into ten (10) groups from the central incisor to second premolar. Following debonding procedure, intra-oral micro-photograph of each tooth was taken using portable digital microscope for assessing the bracket-failure pattern by 4-point scale of adhesive remnant index (ARI). Statistical analysis includedindependent samples t-test for validation study, intraclass correlation coefficient test for intra and inter-examiner reliability, one-way ANOVA to compare in-vivo mean debonding forces between different tooth groups and the non-parametric Kruskal-Wallis test to compare in-vivo ARI between different tooth types. The significance level was set at less than 0.05. The mean debonding force between the universal testing machine (10.43 ± 2.71 N) and the prototype device (9.36 ± 1.65 N) was not significantly different (p = 0.072). The prototype device exhibited excellent intra and inter-examiner reliability (0.942 and 0.921). Significant difference (p < 0.001) of mean debonding force was found between different types of teeth in-vivo. Clinically, ARI scores were not significantly different (p = 0.921) between different groups but overall higher scores were predominant. The prototype device can be recommended for measuring clinical bracket debonding force as the device is validated, proved to be reliable and based on clinical ARI scoring caused less iatrogenic enamel damage. Bracket debonding force should be measured on same tooth from the same arch as significant difference of mean debonding force exists between similar teeth of the upper and lower arches.